The day Jimmy's boa ate the wash - Noble, Trinka Hakes; Kellogg, Steven (New York : Dial Press, 1980)
Jimmy's boa constrictor wreaks havoc on the class trip to a farm.
G3
Keywords: Boa constrictor -- Fiction; Snakes as pets -- Fiction; Farms -- Fiction; Schools -- Fiction